A method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution

By controlling the pH value of the electrochemical dissolving solution of nickel-based high-temperature alloy and using the adsorption effect of modified resin, the problems of low recovery and low purity in the rhenium and molybdenum separation process are solved, and an efficient and environmentally friendly rhenium and molybdenum recovery process is achieved.

CN119177366BActive Publication Date: 2025-02-14JINZHOU VANADIUM IND CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411696793.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-14
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The existing rhenium and molybdenum separation processes have problems such as low recovery, low purity and complex process flow. Especially in the electrochemical dissolving solution of nickel-based high-temperature alloys, the similarity of rhenium and molybdenum makes the separation more difficult.

Method used

By controlling the pH value of the solution, the presence of molybdenum and rhenium ions is different, thereby using the specific adsorption of the modified resin to achieve characteristic adsorption of rhenium and molybdenum. Specific steps include adjusting the pH value, adsorption and desorption using modified MTS9570 resin and MTA1721 resin, and obtaining high-purity metal molybdenum and rhenium by evaporation concentration and recrystallization.

Benefits of technology

It improves the recovery rate and purity of rhenium molybdenum, simplifies the process flow, and achieves efficient resource utilization, and has no waste emissions in the process, which is environmentally friendly, economical and energy-saving.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177366B_ABST
    Figure CN119177366B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of hydrometallurgy, and specifically relates to a method for separating metal molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution, comprising: providing a nickel-based high-temperature alloy electrochemical solution, adjusting the pH value to 0-1.5; adsorbing the nickel-based high-temperature alloy electrochemical solution with a modified MTS9570 resin to obtain a liquid after adsorption of molybdenum, then eluting with a sulfuric acid solution, and then desorbing with an ammonia solution to obtain a molybdenum desorption solution; adjusting the pH value of the liquid after adsorption of molybdenum to 0.5-1.5, adsorbing with a modified MTA1721 resin, eluting with a sulfuric acid solution, first desorbing with an ammonium sulfate and ammonia mixed solution, and then desorbing with an ammonia solution to obtain a two-stage rhenium desorption solution. The molybdenum desorption solution and the two-stage rhenium desorption solution are evaporated, concentrated, crystallized, recrystallized, and reduced with high-temperature hydrogen to obtain metal molybdenum and rhenium. The method for separating rhenium and molybdenum from a nickel-based high-temperature alloy electrochemical solution of the present invention improves the recovery rate of rhenium and molybdenum and the purity of rhenium, and the process is simple and practical.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrometallurgy, and in particular relates to a method for separating metal molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical dissolution solution. Background Art

[0002] Rhenium is a rare metal with a high melting point and has important applications in cutting-edge high-tech fields such as aerospace, nuclear energy and the electronics industry. Rhenium is a scarce metal, and research on its extraction and recovery technology is of great significance to the application of rhenium.

[0003] Metal molybdenum has the advantages of high strength, high melting point, corrosion resistance, and abrasion resistance, and has been widely used in industry. In recent years, the application of molybdenum in high-tech fields has continued to expand, such as machinery, automobiles, aerospace, aviation, space development, petrochemicals, food, anti-corrosion, plastics, composite materials, vacuum engineering, chemical industry, electrical and electronic technology, metallurgical machinery, medicine, agriculture, etc.

[0004] Rhenium and molybdenum are relatively rare metal elements in the earth's crust. Their natural distribution and enrichment state have an important impact on the extraction process. Rhenium is usually associated with metal minerals such as molybdenum and copper, especially in porphyry copper and molybdenum ores, where the rhenium content is often high. However, due to the extremely low abundance of rhenium, usually only a few parts per million, it is extremely challenging to directly extract rhenium from ores.

[0005] In the existing extraction process, the separation of molybdenum and rhenium is a key link. Due to the similarity in chemical properties between the two, such as similar ionic radius, charge state and solubility in certain solvents, they are easy to interfere with each other during the separation process. The main methods for recovering rhenium are precipitation, extraction and ion exchange. The ion exchange method is suitable for recovering rhenium from solutions with low ion concentrations, and it is environmentally friendly and reusable. However, the main impurity elements molybdenum and rhenium in the solution have very similar properties, which makes the ion exchange method rhenium-molybdenum recovery rate low, the process flow is complicated, and the purity of the recovered rhenium is low. Summary of the invention

[0006] The present invention provides a method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution. The method achieves characteristic adsorption of rhenium and molybdenum by controlling the difference in the ionic existence forms of molybdenum and rhenium under the pH value of the solution and by the specific adsorption effect of a modified resin, thereby improving the recovery rate and purity of rhenium and molybdenum. The process is simple, practical and easy to promote.

[0007] A method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution, the specific steps of which are as follows:

[0008] (1) Adjusting pH: Using sodium carbonate solution to adjust the pH value of the rhenium-molybdenum solution to 0-1.5;

[0009] (2) Molybdenum resin adsorption / desorption: The rhenium-containing molybdenum solution adjusted to pH value in step (1) is adsorbed by using a modified MTS9570 resin, wherein the modified MTS9570 resin is obtained by modifying the MTS9570 resin with a phosphoric acid solution, to obtain a molybdenum adsorption liquid; then, phosphoric acid and sulfuric acid solutions are used as eluents to elute the modified MTS9570 resin to obtain a molybdenum eluent, which is returned to step (1) to the rhenium-containing molybdenum solution; and then, an ammonia solution is used to desorb the modified MTS9570 resin after the eluent to obtain a molybdenum desorption liquid;

[0010] (3) Rhenium resin adsorption / desorption: The pH value of the molybdenum adsorption liquid is adjusted to 0.5-1.5 with sulfuric acid solution, and the modified MTA1721 resin is adsorbed thereon, wherein the MTA1721 resin is obtained by modifying the MTA1721 resin with secondary amine; then the modified MTA1721 resin is eluted with sulfuric acid solution as eluent to obtain rhenium eluent, and the solution is returned to step (1) to the rhenium-containing molybdenum solution; the modified MTA1721 resin after elution is first desorbed with a mixed solution of ammonium sulfate and ammonia water, wherein the mass concentration of ammonium sulfate in the mixed solution of ammonium sulfate and ammonia water is 10% and the mass concentration of ammonia water is 0.1%, to obtain a first-stage rhenium desorption liquid, and the solution is returned to step (1); the modified MTA1721 resin after the first-stage desorption is then desorbed with an ammonia solution to obtain a second-stage rhenium desorption liquid;

[0011] (4) Evaporation concentration and crystallization: The molybdenum desorption solution obtained in step (2) is evaporated and concentrated to 1 / 3 of the volume of the molybdenum desorption solution at 120° C. to obtain ammonium molybdate crystals and a molybdenum mother liquor; the molybdenum mother liquor is adjusted to a pH value of 0-1.5 and returned to step (2) to the rhenium-containing molybdenum solution with adjusted pH value; the second-stage rhenium desorption solution obtained in step (3) is evaporated and concentrated to 1 / 3 of the volume of the second-stage rhenium desorption solution at 120° C. to obtain ammonium perrhenate crystals and a rhenium mother liquor; the rhenium mother liquor is adjusted to a pH value of 0.5-1.5 and returned to the solution after the molybdenum absorption in step (3);

[0012] (5) Recrystallization: The ammonium molybdate crystals and the ammonium rhenate crystals obtained in step (4) are respectively dissolved in ultrapure water, and evaporated and crystallized again at a temperature of 120° C. to obtain secondary crystallized ammonium molybdate, secondary crystallized ammonium rhenate, and secondary crystallized ammonium molybdate mother liquor and secondary crystallized ammonium rhenate mother liquor, respectively; the secondary crystallized ammonium molybdate mother liquor is returned to the molybdenum desorption liquid in step (4); the secondary crystallized ammonium rhenate mother liquor is returned to the second-stage rhenium desorption liquid in step (4);

[0013] (6) High-temperature hydrogen reduction: The ammonium molybdate crystals and ammonium rhenate crystals in step (5) are placed in a tubular high-temperature furnace, respectively, and hydrogen is introduced for high-temperature calcination at a temperature of 650°C to prepare metallic molybdenum and metallic rhenium.

[0014] Furthermore, the preparation process of the modified MTS9570 resin is as follows: the cleaned MTS9570 resin is soaked in sulfuric acid for 2 hours, washed with distilled water until the discharged water is close to neutral, then soaked in phosphoric acid solution for 12 hours, washed with water until the pH of the discharged water is 6, and drained.

[0015] Furthermore, the concentration of the sulfuric acid is 2 mol / L, and the amount of the sulfuric acid is 3-5 times the volume of the resin; the concentration of the phosphoric acid solution is 2 mol / L, and the amount of the phosphoric acid solution is 3-5 times the volume of the resin.

[0016] Furthermore, the preparation process of the modified MTA1721 resin is as follows: soaking the cleaned MTA1721 resin in a secondary amine for 12 hours, washing with water until the discharged water is neutral, and draining the water.

[0017] Furthermore, the amount of the secondary amine is 3-5 times the volume of the resin.

[0018] Furthermore, the rhenium-molybdenum-containing solution is a nickel-based high-temperature alloy electrochemical dissolution solution.

[0019] Furthermore, the mass concentration of the ammonia solution in step (2) and step (3) is 10%; the amount of the ammonia solution is 3 times the volume of the desorbed resin, and the hourly flow rate of the ammonia solution is 2-4 times the volume of the resin.

[0020] Furthermore, in step (2) and step (3), the pH of the eluent sulfuric acid solution is 2; the amount of sulfuric acid solution used is 5 times the volume of the resin to be eluted, and the hourly flow rate of the sulfuric acid solution is 4 times the volume of the resin.

[0021] Furthermore, the dosage of the ammonium sulfate and ammonia water mixed solution is 10 times the volume of the MTA1721 resin, and the hourly flow rate of the ammonium sulfate and ammonia water mixed solution is 1-2 times the volume of the resin.

[0022] Furthermore, in step (1), the mass concentration of the sodium carbonate solution is 9%, and in steps (3) and (4), a sulfuric acid solution is used to adjust the pH value.

[0023] Advantages and positive effects of the present invention:

[0024] 1. The present invention adopts the resin adsorption method, and the rhenium and molybdenum in the solution are ReO4 - and MoO4 2- It exists in the form of anions. When pH ≤ 2.5, Mo exists in the form of cations. The molybdenum resin is chelated with phosphate to make the resin more selective for molybdenum. At the same time, the rhenium resin is impregnated with secondary amines to make the resin more selective for rhenium.

[0025] 2. The present invention adopts a method of resin grafting functional groups to improve the selectivity of the two resins for rhenium and molybdenum, so it can treat various acidic nickel-based high-temperature alloy electrochemical dissolution solutions and use a wide range of raw materials.

[0026] 3. After the rhenium and molybdenum in the solution are effectively enriched, the molybdenum resin is directly desorbed with ammonia water to obtain ammonium molybdate. About 5% of the molybdenum is not adsorbed by the molybdenum resin and enters the rhenium resin. The desorption of the rhenium resin is divided into two stages. The first stage uses 0.1% ammonia water + 10% ammonium sulfate to desorb molybdenum. The obtained desorption liquid is acidified and then continues to be adsorbed by the molybdenum resin. The second stage uses 10% ammonia water to desorb ammonium perrhenate. The purity of ammonium molybdate is 99.8%, and the purity of ammonium rhenate is 99.9%.

[0027] 4. High-purity ammonium molybdate and ammonium perrhenate are obtained by evaporation concentration and recrystallization, with purities of 99.99% and 99.999% respectively.

[0028] 5. The reasonable process combination of the present invention allows rhenium and molybdenum to be recovered and effectively utilized, achieving the goals of environmental protection, economy, energy saving, and high resource utilization. The ion exchange resin process used has low energy consumption, and the entire process basically has no three wastes discharged. All resources are utilized with maximum efficiency, and the resulting products are convenient for subsequent treatment and processing. Therefore, the present invention has the advantages of environmental protection, economy, energy saving, and high resource utilization. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The process flow chart of an embodiment of the present invention. DETAILED DESCRIPTION

[0030] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.

[0031] The following adsorption rate calculation method

[0032] Calculation of adsorption process: Taking molybdenum as an example, the concentration of molybdenum in the feed solution (C0, mg / L), the concentration of molybdenum in the solution after molybdenum adsorption (C1, mg / L), and the concentration of molybdenum in the solution after desorption (C2, mg / L) were determined by inductively coupled plasma optical emission spectrometry (ICP-OES), and the adsorption rate E of molybdenum was calculated using formula (1-1).

[0033]

[0034] The following embodiment of the method for separating rhenium and molybdenum from the electrochemical solution of nickel-based high-temperature alloy can be found in Figure 1 .

[0035] Example 1

[0036] The high-temperature alloy leaching solution of a high-temperature alloy recovery plant, specifically a nickel-based high-temperature alloy electrochemical dissolution solution in this embodiment, has the following main elements: nickel 80g / L, cobalt 3.6g / L, aluminum 3.2g / L, chromium 2.8g / L, rhenium 1.8g / L, molybdenum 1.2g / L, tantalum 20mg / L, and tungsten 120mg / L.

[0037] Preparation method of modified MTS9570 resin: wash the MTS9570 resin repeatedly with 50-60℃ hot water, soak the filtered resin in 2mol / L sulfuric acid for 2h (the amount of sulfuric acid is 5 times the volume of the resin), wash with distilled water until the discharged water is close to neutral, soak it in 2mol / L phosphoric acid solution for 12h (the amount of phosphoric acid solution is 5 times the volume of the resin), and wash with distilled water until the pH of the discharged water is 6, and drain the water;

[0038] Preparation method of modified MTA1721 resin: wash repeatedly with 50-60℃ hot water, soak the filtered resin with secondary amine for 12h (the amount of secondary amine is 5 times the volume of the resin), wash with distilled water until the discharged water is neutral, and drain the water;

[0039] The method for separating rhenium and molybdenum from the electrochemical solution of nickel-based high-temperature alloy in this embodiment is as follows:

[0040] (1) Adjusting pH: Using a sodium carbonate solution with a mass concentration of 9% to adjust the pH value of the nickel-based high-temperature alloy electrochemical solution to 0;

[0041] (2) Molybdenum resin adsorption / desorption: The modified MTS9570 resin is used to adsorb the electrochemical solution of the nickel-based high-temperature alloy with a pH value of 0 to obtain a molybdenum-adsorbed solution; then, the modified MTS9570 resin is eluted with a sulfuric acid solution (pH=2) as an eluent to obtain a molybdenum eluent, which is returned to step (1) and mixed with the electrochemical solution of the nickel-based high-temperature alloy; then, the modified MTS9570 resin after elution is desorbed with an ammonia solution with a mass concentration of 10% to obtain a molybdenum desorption solution, which is sent for evaporation and crystallization treatment;

[0042] The amount of sulfuric acid solution is 5 times the volume of the resin, and the flow rate per hour is 4 times the volume of the resin (here it means that if the volume of the resin is 1m 3 , then the flow rate of sulfuric acid solution is 4m 3 / h); the amount of ammonia solution is 3 times the volume of resin, and the flow rate per hour is 4 times the volume of resin;

[0043] (3) Rhenium resin adsorption / desorption: The pH value of the molybdenum adsorption liquid is adjusted to 0.5 with sulfuric acid solution, and the modified MTA1721 resin is used to adsorb it; then sulfuric acid solution (pH = 2) is used as eluent (the amount of sulfuric acid solution is 5 times the resin volume, and the flow rate is 4 times the resin volume per hour) to elute the modified MTA1721 resin to obtain rhenium eluent, which is returned to step (1) and mixed with the nickel-based high-temperature alloy electrochemical dissolution solution; first, it is desorbed with ammonium sulfate and ammonia water mixture (10%wt ammonium sulfate + 0.1%wt ammonia water, 10 times the resin volume, and the flow rate is 2 times the resin volume per hour) to obtain a first-stage rhenium desorption liquid, and then returned to step (1); then, it is desorbed with ammonia water solution with a mass concentration of 10% (3 times the resin volume, 4 times the resin volume) to obtain a second-stage rhenium desorption liquid, which is sent for evaporation and crystallization treatment;

[0044] (4) Evaporation concentration and crystallization: The obtained molybdenum desorption solution is concentrated by evaporation at 120° C. to 1 / 3 of the volume of the molybdenum desorption solution, to obtain ammonium molybdate crystals and a molybdenum mother liquor; the pH value of the molybdenum mother liquor is adjusted to 0 with a sulfuric acid solution, and the process returns to step (2) of molybdenum adsorption; the obtained second-stage rhenium desorption solution is concentrated by evaporation at 120° C. to 1 / 3 of the volume of the second-stage rhenium desorption solution, to obtain ammonium perrhenate crystals and a rhenium mother liquor; the pH value of the rhenium mother liquor is adjusted to 0.5 with a sulfuric acid solution, and the process returns to step (3) of rhenium adsorption;

[0045] (5) Recrystallization: The ammonium molybdate crystals and the ammonium rhenate crystals obtained in step (4) are respectively dissolved in ultrapure water, and evaporated and crystallized again at a temperature of 120° C. to obtain secondary crystallized ammonium molybdate, secondary crystallized ammonium rhenate, and secondary crystallized ammonium molybdate mother liquor and secondary crystallized ammonium rhenate mother liquor, respectively;

[0046] The mother liquor of the secondary crystallized ammonium molybdate is returned to the molybdenum desorption solution in step (4); the mother liquor of the secondary crystallized ammonium rhenate is returned to the second-stage rhenium desorption solution in step (4);

[0047] (6) High-temperature hydrogen reduction: The ammonium molybdate crystals and ammonium rhenate crystals in step (5) are placed in a tubular high-temperature furnace, respectively, at a reaction temperature of 650°C, and hydrogen is introduced to obtain metallic molybdenum and metallic rhenium.

[0048] After testing: the adsorption rates of molybdenum and rhenium in the modified MTS9570 resin (molybdenum resin) during the adsorption process were 94.6% and 1.3% respectively; the element concentrations in the molybdenum desorption solution were: molybdenum 4g / L, rhenium 0.03g / L.

[0049] The adsorption rates of modified MTA1721 resin (rhenium resin) for rhenium and molybdenum were 97.5% and 0.7% respectively. The element concentrations in the first stage rhenium desorption solution were: rhenium 1.5g / L, molybdenum 0.025g / L. The element concentrations in the second stage rhenium desorption solution were: rhenium 18g / L, molybdenum 5mg / L.

[0050] The purities of the ammonium molybdate crystals and ammonium rhenate crystals obtained after recrystallization are 99.9991% and 99.99995%, respectively.

[0051] The purities of metallic molybdenum and rhenium obtained by high-temperature hydrogen reduction are 99.9996% and 99.999992% respectively.

[0052] Example 2

[0053] High-temperature alloy leaching solution of a high-temperature alloy recycling plant, specifically a nickel-based high-temperature alloy electrochemical dissolution solution in this embodiment, main elements: nickel 60g / L, cobalt 6.2g / L, aluminum 7.2g / L, chromium 4.8g / L, rhenium 1.1g / L, molybdenum 1.6g / L, tantalum 20mg / L, tungsten 640mg / L, hafnium 130mg / L;

[0054] Preparation method of modified MTS9570 resin: wash the MTS9570 resin repeatedly with 50-60℃ hot water, soak the filtered resin in 2mol / L sulfuric acid for 2h (the amount of sulfuric acid is 3 times the volume of the resin), wash with distilled water until the discharged water is close to neutral, soak it in 2mol / L phosphoric acid solution for 12h (the amount of phosphoric acid solution is 3 times the volume of the resin), and wash it with distilled water until the pH of the discharged water is 6, and drain the water;

[0055] Preparation method of modified MTA1721 resin: wash repeatedly with 50-60℃ hot water, soak the filtered resin with secondary amine for 12h (the amount of secondary amine is 3 times the volume of the resin), wash with distilled water until the discharged water is neutral, and drain the water;

[0056] The method for separating rhenium and molybdenum from the electrochemical solution of nickel-based high-temperature alloy in this embodiment is as follows:

[0057] (1) Adjusting pH: Using a sodium carbonate solution with a mass concentration of 9%, the pH value of the electrochemical solution of the nickel-based high-temperature alloy is adjusted to pH = 1.0;

[0058] (2) Molybdenum resin adsorption / desorption: The modified MTS9570 resin is used to adsorb the electrochemical solution of the nickel-based high-temperature alloy with a pH value of 1.0 to obtain a molybdenum-adsorbed solution; then, the modified MTS9570 resin is eluted with a sulfuric acid solution (pH=2) as an eluent to obtain a molybdenum eluent, which is returned to step (1) and mixed with the electrochemical solution of the nickel-based high-temperature alloy; then, the modified MTS9570 resin after elution is desorbed with an ammonia solution with a mass concentration of 10% to obtain a molybdenum desorption solution, which is sent for evaporation and crystallization treatment;

[0059] Among them, the amount of sulfuric acid solution is 5 times the volume of resin, and the flow rate per hour is 4 times the volume of resin; the amount of ammonia solution is 3 times the volume of resin, and the flow rate per hour is 2 times the volume of resin;

[0060] (3) Rhenium resin adsorption / desorption: The pH value of the molybdenum adsorption liquid is adjusted to 1.5 with sulfuric acid solution, and the modified MTA1721 resin is used to adsorb it; then sulfuric acid solution (pH=2) is used as an eluent (wherein, the amount of sulfuric acid solution is 5 times the resin volume, and the flow rate is 4 times the resin volume per hour) to elute the modified MTA1721 resin to obtain a rhenium eluent, and return to step (1); first use an ammonium sulfate and ammonia water mixture (10%wt ammonium sulfate + 0.1%wt ammonia water, 10 times the resin volume, and the flow rate is 1 times the resin volume per hour) for desorption to obtain a first-stage rhenium desorption liquid, return to step (1) and mix with the nickel-based high-temperature alloy electrochemical dissolution liquid; then use a 10% ammonia water solution for desorption (3 times the resin volume, 2 times the resin volume) to obtain a second-stage rhenium desorption liquid, which is sent for evaporation and crystallization treatment;

[0061] (4) Evaporation and concentration, crystallization: The obtained molybdenum desorption solution is concentrated by evaporation at 120° C. to 1 / 3 of the volume of the molybdenum desorption solution, to obtain ammonium molybdate crystals and a molybdenum mother liquor; the pH value of the molybdenum mother liquor is adjusted to 1.0 with a sulfuric acid solution, and the process returns to step (2) of molybdenum adsorption; the obtained second-stage rhenium desorption solution is concentrated by evaporation at 120° C. to 1 / 3 of the volume of the second-stage rhenium desorption solution, to obtain ammonium perrhenate crystals and a rhenium mother liquor; the pH value of the rhenium mother liquor is adjusted to 1.5 with a sulfuric acid solution, and the process returns to step (3) of rhenium adsorption;

[0062] (5) Recrystallization: The ammonium molybdate crystals and the ammonium rhenate crystals obtained in step (4) are respectively dissolved in ultrapure water, and evaporated and crystallized again at a temperature of 120° C. to obtain secondary crystallized ammonium molybdate, secondary crystallized ammonium rhenate, and secondary crystallized ammonium molybdate mother liquor and secondary crystallized ammonium rhenate mother liquor, respectively;

[0063] The mother liquor of the secondary crystallized ammonium molybdate is returned to the molybdenum desorption solution in step (4); the mother liquor of the secondary crystallized ammonium rhenate is returned to the second-stage rhenium desorption solution in step (4);

[0064] (6) High-temperature hydrogen reduction: The ammonium molybdate crystals and ammonium rhenate crystals in step (5) are placed in a tubular high-temperature furnace, respectively, at a reaction temperature of 650°C, and hydrogen is introduced to obtain metallic molybdenum and metallic rhenium.

[0065] After testing: the adsorption rates of molybdenum and rhenium in the modified MTS9570 resin (molybdenum resin) adsorption process were 95.2% and 0.8% respectively, and the element concentrations in the molybdenum desorption solution were: molybdenum 5.2g / L, rhenium 0.046g / L.

[0066] The adsorption rates of modified MTA1721 resin (rhenium resin) for rhenium and molybdenum were 96.5% and 0.3% respectively. The element concentrations in the first rhenium desorption solution were: rhenium 1.1g / L, molybdenum 0.065g / L. The element concentrations in the second rhenium desorption solution were: rhenium 12g / L, molybdenum 2mg / L.

[0067] The purities of the ammonium molybdate crystals and ammonium rhenate crystals obtained after recrystallization are 99.9991% and 99.99997%, respectively.

[0068] The purities of metallic molybdenum and rhenium obtained by high-temperature hydrogen reduction are 99.9994% and 99.999993% respectively.

[0069] Example 3

[0070] A high-temperature alloy leachate containing rhenium-molybdenum waste liquid from a smelter, specifically a nickel-based high-temperature alloy electrochemical dissolution solution in this embodiment: 40 g / L cobalt, 1.2 g / L aluminum, 1.8 g / L chromium, 0.78 g / L rhenium, 0.6 g / L molybdenum, and 640 mg / L tungsten;

[0071] Preparation method of modified MTS9570 resin: wash the MTS9570 resin repeatedly with 50-60℃ hot water, soak the filtered resin in 2mol / L sulfuric acid for 2h (the amount of sulfuric acid is 4 times the volume of the resin), wash with distilled water until the discharged water is close to neutral, soak it in 2mol / L phosphoric acid solution for 12h (the amount of phosphoric acid solution is 4 times the volume of the resin), and wash with distilled water until the pH of the discharged water is 6, and drain the water;

[0072] Preparation method of modified MTA1721 resin: wash repeatedly with 50-60℃ hot water, soak the filtered resin with secondary amine for 12h (the amount of secondary amine is 4 times the volume of the resin), wash with distilled water until the discharged water is neutral, and drain the water;

[0073] The method for separating rhenium and molybdenum from the electrochemical solution of nickel-based high-temperature alloy in this embodiment is as follows:

[0074] (1) Adjusting pH: Using 9% sodium carbonate solution, adjust the pH value of the electrochemical solution of the nickel-based high-temperature alloy to pH = 1.5;

[0075] (2) Molybdenum resin adsorption / desorption: The modified MTS9570 resin is used to adsorb the electrochemical solution of the nickel-based high-temperature alloy with a pH value of 1.5 to obtain a molybdenum-absorbed solution; then, a sulfuric acid solution (pH=2) is used as an eluent (wherein, the amount of sulfuric acid solution is 5 times the volume of the resin, and the flow rate is 4 times the volume of the resin per hour) to elute the modified MTS9570 resin to obtain a molybdenum eluent, which is returned to step (1) and mixed with the electrochemical solution of the nickel-based high-temperature alloy; then, the modified MTS9570 resin after elution is desorbed with an ammonia solution with a mass concentration of 10% to obtain a molybdenum desorption solution, which is sent for evaporation and crystallization treatment;

[0076] Among them, the amount of sulfuric acid solution is 5 times the volume of resin, and the flow rate per hour is 4 times the volume of resin; the amount of ammonia solution is 3 times the volume of resin, and the flow rate per hour is 2 times the volume of resin;

[0077] (3) Rhenium resin adsorption / desorption: The pH value of the molybdenum adsorption solution is adjusted to 0.5 with sulfuric acid solution, and the modified MTA1721 resin is used to adsorb it; then, the modified MTA1721 resin is eluted with sulfuric acid solution (pH=2) as an eluent to obtain a rhenium eluent, which is returned to step (1) and mixed with the nickel-based high-temperature alloy electrochemical dissolution solution;

[0078] First, desorb with a mixture of ammonium sulfate and ammonia water (10%wt ammonium sulfate + 0.1%wt ammonia water, 10 times the volume of the resin, 1 times the volume of the resin per hour) to obtain a first-stage rhenium desorption solution, and return to step (1); then desorb with an ammonia solution with a mass concentration of 10% (3 times the volume of the resin, 2 times the volume of the resin) to obtain a second-stage rhenium desorption solution, which is sent for evaporation and crystallization treatment;

[0079] (4) Evaporation and concentration, crystallization: The obtained molybdenum desorption solution is concentrated by evaporation at 120° C. to 1 / 3 of the volume of the molybdenum desorption solution, to obtain ammonium molybdate crystals and a molybdenum mother liquor; the pH value of the molybdenum mother liquor is adjusted to 1.5 with a sulfuric acid solution, and the process returns to step (2) of molybdenum adsorption; the obtained second-stage rhenium desorption solution is concentrated by evaporation at 120° C. to 1 / 3 of the volume of the second-stage rhenium desorption solution, to obtain ammonium perrhenate crystals and a rhenium mother liquor; the pH value of the rhenium mother liquor is adjusted to 0.5 with a sulfuric acid solution, and the process returns to step (3) of rhenium adsorption;

[0080] (5) Recrystallization: The ammonium molybdate crystals and the ammonium rhenate crystals obtained in step (4) are respectively dissolved in ultrapure water, and evaporated and crystallized again at a temperature of 120° C. to obtain secondary crystallized ammonium molybdate, secondary crystallized ammonium rhenate, and secondary crystallized ammonium molybdate mother liquor and secondary crystallized ammonium rhenate mother liquor, respectively;

[0081] The mother liquor of the secondary crystallized ammonium molybdate is returned to the molybdenum desorption solution in step (4); the mother liquor of the secondary crystallized ammonium rhenate is returned to the second-stage rhenium desorption solution in step (4);

[0082] (6) High-temperature hydrogen reduction: The ammonium molybdate crystals and ammonium rhenate crystals in step (5) are placed in a tubular high-temperature furnace, respectively, at a reaction temperature of 650°C, and hydrogen is introduced to prepare metallic molybdenum and metallic rhenium.

[0083] After testing: the adsorption rates of molybdenum and rhenium in the modified MTS9570 resin (molybdenum resin) adsorption process were 97% and 0.2% respectively, and the element concentrations in the molybdenum desorption solution were: molybdenum 1.7g / L, rhenium 0.016g / L.

[0084] The adsorption rates of modified MTA1721 resin (rhenium resin) for rhenium and molybdenum were 94% and 0.32% respectively. The element concentrations in the first stage rhenium desorption solution were: rhenium 0.2g / L, molybdenum 0.042g / L. The element concentrations in the second stage rhenium desorption solution were: rhenium 8.7g / L, molybdenum 2mg / L.

[0085] The purities of the ammonium molybdate crystals and ammonium rhenate crystals obtained after recrystallization are 99.9991% and 99.99994%, respectively.

[0086] The purities of metallic molybdenum and rhenium obtained by high-temperature hydrogen reduction are 99.9999% and 99.999996% respectively.

[0087] The difference between Comparative Example 1 and Example 1 is that unmodified MTS9570 resin and unmodified TA1721 resin are used, and the rest is the same as Example 1.

[0088] After testing: the adsorption rates of molybdenum and rhenium in the adsorption process of unmodified MTS9570 resin (molybdenum resin) were 87.1% and 10.3% respectively; the element concentrations in the molybdenum desorption solution were: molybdenum 3.4g / L, rhenium 0.45g / L.

[0089] The adsorption rates of unmodified MTA1721 resin (rhenium resin) for rhenium and molybdenum were 81.6% and 4.8% respectively. The element concentrations in the first rhenium desorption solution were: rhenium 1.2g / L, molybdenum 0.095g / L. The element concentrations in the second rhenium desorption solution were: rhenium 15.4g / L, molybdenum 27mg / L.

[0090] The purities of the ammonium molybdate crystals and ammonium rhenate crystals obtained after recrystallization are 97.14% and 96.05%, respectively.

[0091] The difference between Comparative Example 2 and Example 1 is that in step (1), the pH value of the nickel-based high-temperature alloy electrochemical dissolution solution is adjusted to 3 using 9% sodium carbonate solution, and the rest is the same as Example 1.

[0092] After testing: the adsorption rates of molybdenum and rhenium in the modified MTS9570 resin (molybdenum resin) during the adsorption process were 67.4% and 1.1% respectively; the element concentrations in the molybdenum desorption solution were: molybdenum 3.1g / L, rhenium 0.025g / L.

[0093] The adsorption rates of modified MTA1721 resin (rhenium resin) for rhenium and molybdenum were 65.1% and 0.52% respectively. The element concentrations in the first rhenium desorption solution were: rhenium 1.0g / L, molybdenum 0.02g / L. The element concentrations in the second rhenium desorption solution were: rhenium 11g / L, molybdenum 12mg / L.

[0094] The adsorption rate of rhenium and molybdenum is low and the effect is poor.

[0095] The difference between Comparative Example 3 and Example 1 is that step (3) does not include a step of performing a rhenium desorption using a mixed solution of ammonium sulfate and ammonia water, that is, only a 10% ammonia water solution is used for desorption, and the rest is the same as Example 1;

[0096] After testing, the element concentrations in the first stage rhenium desorption solution were: rhenium 1.4g / L, molybdenum 5mg / L. The element concentrations in the second stage rhenium desorption solution were: rhenium 17.5g / L, molybdenum 0.022g / L.

[0097] The purity of the ammonium rhenate crystals obtained after recrystallization is only 99.04%.

[0098] The difference between Comparative Example 4 and Example 1 is that the order of step (2) and step (3) is reversed, that is, the modified MTA1721 resin is used for adsorption first, and then the modified MTS9570 resin is used for adsorption. The other steps are the same as those of Example 1.

[0099] After testing: the adsorption rates of modified MTA1721 resin (rhenium resin) for rhenium and molybdenum were 91.4% and 17.4% respectively. The element concentrations in the first stage rhenium desorption solution were: rhenium 1.41g / L, molybdenum 0.76g / L. The element concentrations in the second stage rhenium desorption solution were: rhenium 15.2g / L, molybdenum 87mg / L.

[0100] The adsorption rates of molybdenum and rhenium in the adsorption process of modified MTS9570 resin (molybdenum resin) were 94.6% and 0.1% respectively; the element concentrations in the molybdenum desorption solution were: molybdenum 2.4g / L, rhenium 0.02g / L.

[0101] The purities of the ammonium molybdate crystals and ammonium rhenate crystals obtained after recrystallization are 99.9991% and 84.6673%, respectively.

[0102] The purities of metallic molybdenum and rhenium obtained by high-temperature hydrogen reduction are 99.9993% and 85.782% respectively.

[0103] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution, characterized in that: Specific steps as follows: (1) Adjusting pH: Using sodium carbonate solution to adjust the pH value of the rhenium-molybdenum solution to 0-1.5; (2) Molybdenum resin adsorption / desorption: The rhenium-containing molybdenum solution adjusted in pH value in step (1) is adsorbed by using modified MTS9570 resin, wherein the rhenium-containing molybdenum solution is a nickel-based high-temperature alloy electrochemical dissolution solution, and the modified MTS9570 resin is obtained by modifying MTS9570 resin with sulfuric acid and phosphoric acid solutions to obtain a molybdenum adsorption liquid; then, the modified MTS9570 resin is eluted with sulfuric acid solution as an eluent to obtain a molybdenum eluent, which is returned to step (1) to the rhenium-containing molybdenum solution; Then, the modified MTS9570 resin after elution is desorbed with an ammonia solution to obtain a molybdenum desorption solution; (3) Rhenium resin adsorption / desorption: The pH value of the molybdenum adsorption liquid is adjusted to 0.5-1.5 with sulfuric acid solution, and the modified MTA1721 resin is adsorbed thereon, wherein the MTA1721 resin is obtained by modifying the MTA1721 resin with secondary amine; then the modified MTA1721 resin is eluted with sulfuric acid solution as eluent to obtain rhenium eluent, and the solution is returned to step (1) to the rhenium-containing molybdenum solution; the modified MTA1721 resin after elution is first desorbed with a mixed solution of ammonium sulfate and ammonia water, wherein the mass concentration of ammonium sulfate in the mixed solution of ammonium sulfate and ammonia water is 10% and the mass concentration of ammonia water is 0.1%, to obtain a first-stage rhenium desorption liquid, and the solution is returned to step (1); the modified MTA1721 resin after the first-stage desorption is then desorbed with an ammonia solution to obtain a second-stage rhenium desorption liquid; The preparation process of the modified MTS9570 resin is as follows: soaking the cleaned MTS9570 resin in sulfuric acid for 2 hours, washing with distilled water until the discharged water is close to neutral, soaking in phosphoric acid solution for 12 hours, washing with water until the discharged water has a pH of 6, and draining the water; The preparation process of the modified MTA1721 resin is as follows: soaking the cleaned MTA1721 resin in a secondary amine for 12 hours, washing with water until the discharged water is neutral, and draining the water; (4) Evaporation concentration and crystallization: The molybdenum desorption solution obtained in step (2) is evaporated and concentrated to 1 / 3 of the volume of the molybdenum desorption solution at 120° C. to obtain ammonium molybdate crystals and a molybdenum mother liquor; the molybdenum mother liquor is adjusted to a pH value of 0-1.5 and returned to step (2) to the rhenium-containing molybdenum solution with adjusted pH value; the second-stage rhenium desorption solution obtained in step (3) is evaporated and concentrated to 1 / 3 of the volume of the second-stage rhenium desorption solution at 120° C. to obtain ammonium perrhenate crystals and a rhenium mother liquor; the rhenium mother liquor is adjusted to a pH value of 0.5-1.5 and returned to the solution after the molybdenum absorption in step (3); (5) Recrystallization: The ammonium molybdate crystals and the ammonium rhenate crystals obtained in step (4) are respectively dissolved in ultrapure water, and evaporated and crystallized again at a temperature of 120° C. to obtain secondary crystallized ammonium molybdate, secondary crystallized ammonium rhenate, and secondary crystallized ammonium molybdate mother liquor and secondary crystallized ammonium rhenate mother liquor, respectively; the secondary crystallized ammonium molybdate mother liquor is returned to the molybdenum desorption liquid in step (4); the secondary crystallized ammonium rhenate mother liquor is returned to the second-stage rhenium desorption liquid in step (4); (6) High-temperature hydrogen reduction: The ammonium molybdate crystals and ammonium rhenate crystals in step (5) are placed in a tubular high-temperature furnace, respectively, and hydrogen is introduced for high-temperature calcination at a temperature of 650°C to prepare metallic molybdenum and metallic rhenium.

2. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, wherein: The concentration of the sulfuric acid is 2 mol / L, and the amount of the sulfuric acid used is 3-5 times the volume of the resin; the concentration of the phosphoric acid solution is 2 mol / L, and the amount of the phosphoric acid solution used is 3-5 times the volume of the resin.

3. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, characterized in that: The amount of the secondary amine used is 3-5 times the volume of the resin.

4. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, characterized in that: The mass concentration of the ammonia solution in step (2) and step (3) is 10%; the amount of the ammonia solution is 3 times the volume of the desorbed resin, and the hourly flow rate of the ammonia solution is 2-4 times the volume of the resin.

5. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, characterized in that: In step (2) and step (3), the pH of the eluting solution of sulfuric acid is 2; the amount of sulfuric acid solution is 5 times the volume of the resin to be eluted, and the hourly flow rate of the sulfuric acid solution is 4 times the volume of the resin.

6. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, characterized in that: The dosage of the ammonium sulfate and ammonia water mixed solution is 10 times the volume of the MTA1721 resin, and the hourly flow rate of the ammonium sulfate and ammonia water mixed solution is 1-2 times the volume of the resin.

7. The method for separating metallic molybdenum and rhenium from a nickel-based high-temperature alloy electrochemical solution according to claim 1, characterized in that: In step (1), the mass concentration of the sodium carbonate solution is 9%, and in steps (3) and (4), a sulfuric acid solution is used to adjust the pH value.

Citation Information

Patent Citations

  • Method for extracting rhenium from eluate of flue ash generated by baking enriched ore of molybdenum

    CN101050489A

  • Method for recovering rhenium from high-temperature alloy pickle liquor

    CN103789552A